Climate change and epilepsy: Time to take action. Issue 4 (20th September 2019) - Sisodiya, Sanjay M.; Fowler, Hayley J.; Lake, Iain; Nanji, Rosemary O.; Gawel, Kinga; Esguerra, Camila V.; Newton, Charles; Foley, Aideen
Abstract: Climate change is the biggest challenge facing humanity today. The associated global warming and humidification, increases in the severity and frequency of extreme climate events, extension of the ranges of vector‐borne diseases, and the consequent social and economic stresses and disruption will have major negative consequences on many aspects of health care. People whose resilience to change is already impaired may suffer disproportionately from these environmental changes, which are of unprecedented reach and magnitude. There has been little connection made so far between climate change and epilepsy. We briefly review the history of climate change science and the subsequent response of the global scientific community. We consider how climate change effects might in general affect health and disease. We consider some of the underlying complex interactions that, for example, favor the spread of vector‐borne diseases and how climate models operate and may help plan for global and local changes. We then speculate specifically on how these generic ideas may apply specifically to epilepsy. We consider these impacts at levels from molecular to the epidemiological. Data are sparse, and there is undoubtedly a need for more information to enable better estimation of possible effects of climate change on care in epilepsy. We also consider how the professional activities of those involved in epilepsy health care might contribute to global carbon emissions, for example, through flying for conference attendance. Healthcare organizations across the world are already considering, and responding to, many of these issues. We argue for more research in this area, but also for action today. Actions today are likely to generate cobenefits for health care, including care in epilepsy, resulting from efforts to decarbonize, mitigate effects of climate change that has already happened, and plan for adaptation to climate change.